1999
DOI: 10.1159/000017108
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Assessment and Associations of Falls in Dementia with Lewy Bodies and Alzheimer’s Disease

Abstract: Falls were assessed for 3 months using a daily fall diary in 65 (30 dementia with Lewy bodies, DLB; 35 Alzheimer’s disease, AD) dementia patients from a case register, diagnosed using operationalised clinical criteria, with established accuracy against post-mortem. Multiple falls (>5) occurred in 37% of DLB patients and 6% of those with AD, often resulting in injury. None of the standard risk assessment tools identified fallers, but they did identify multiple fallers. More detailed evaluation methods examining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 18 publications
2
89
0
4
Order By: Relevance
“…These found relative risks (RRs) of 2.4 (95% CI 1.9 to 2.9), 9 2.6 (no CI given), 10 and 2.5 (1.9 to 3.4) 6 and ORs of 3.7 (1.3 to 10.0) 11 and 2.4 (1.3 to 4.4). 12 Among 10 Class II studies, ORs were 3.0 (1.3 to 7.3), 13 16.0 (4.4 to 58.0), 14 5.0 (1.2 to 20.9), 15 2.0 (1.2 to 3.5), 16 3.5 (1.2 to 9.6), 17 2.4 (1.3 to 4.4), 12 5.4 (1.8 to 15.7), 18 3.1 (2.2 to 4.4), 19 12.5 (3.0 to 52.2), 20 and 4.0 (1.3 to 12.1). 21 Other Class II follow-up studies reported RRs of 1.9 (1.3 to 2.9) and 1.8 (1.3 to 2.4), 22 and 2.0 (1.3 to 3.1).…”
Section: Analysis Of Evidence Risk Of Falls Deter-mentioning
confidence: 99%
“…These found relative risks (RRs) of 2.4 (95% CI 1.9 to 2.9), 9 2.6 (no CI given), 10 and 2.5 (1.9 to 3.4) 6 and ORs of 3.7 (1.3 to 10.0) 11 and 2.4 (1.3 to 4.4). 12 Among 10 Class II studies, ORs were 3.0 (1.3 to 7.3), 13 16.0 (4.4 to 58.0), 14 5.0 (1.2 to 20.9), 15 2.0 (1.2 to 3.5), 16 3.5 (1.2 to 9.6), 17 2.4 (1.3 to 4.4), 12 5.4 (1.8 to 15.7), 18 3.1 (2.2 to 4.4), 19 12.5 (3.0 to 52.2), 20 and 4.0 (1.3 to 12.1). 21 Other Class II follow-up studies reported RRs of 1.9 (1.3 to 2.9) and 1.8 (1.3 to 2.4), 22 and 2.0 (1.3 to 3.1).…”
Section: Analysis Of Evidence Risk Of Falls Deter-mentioning
confidence: 99%
“…Supine systolic hypertension is often present in older patients with orthostatic hypotension [368][369][370][371][372] . Hypotension may increase the risk of cerebral ischaemia from sudden declines in blood pressure [373,374] , but it also complicates treatment, given that most agents used for treatment of orthostatic hypotension will exacerbate supine hypotension [371,375] . Carotid sinus hypersensitivity is an age-related diagnosis, rare before age 40; the prevalence increases with advancing years and with cardiovascular, cerebrovascular and neurodegenerative co-morbidity [76,77,83,376] .…”
Section: Syncope In the Older Adult Backgroundmentioning
confidence: 99%
“…Orthostatic blood pressure measurements, carotid sinus massage and head-up tilt studies are well-tolerated tests, even in the frail elderly with cognitive impairment [373,374] . If patients have difficulty standing unaided, the head-up tilt can be used to assess orthostatic blood pressure changes [49] .…”
Section: Evaluation Of the Frail Elderlymentioning
confidence: 99%
“…ADL의 저하는 보호자 부담(caregiver burden)을 가중시키며, ADL 저하 중에서 특히 대소변 가리기, 화장실 이용하기, 혼자 식사하기 등이 중요한 요인으로 알려져 있다 [23]. ADL의 저하는 치매 환자의 낙상과 유의한 관계가 있으며 [24], 또한 치매 환자의 의료비의 상승, 시설 입소의 요구를 증대시키는 핵심적인 요소이다 [1,25]. …”
Section: ) 치매의 발병과의 관계unclassified